Improve POS(Point of Sales) Efficiency in a Super Market Using Smart Technologies - Yamuna.G.K, Chandana.R, Dr. Dayanand Lal, V. Saipreethi, SriLakshmi D (International Journal of Control and Automation, 2020)
People get their daily essentials in supermarkets people going to supermarkets has been increased day by day. Without any technology it is difficult to manage. At present they are using Barcode scanning technology but this takes a lot of time for the consumer to wait before all of the items are checked and the bill produced.Even the cost of the products may vary during the festival season as a discount of the product may be added without using any technique it is difficult to handle. To avoid this scenario, we proposed a device that consists of RFID tag, RFID Reader, LCD, android, Wi-Fi and cloud access. The required products of the customer will be placed in the trolley where they are tracked using the RFID reader and product name, cost, expiry date, discount, and the total cost will be displayed on the LCD and in the Android app if the customer has logged in the application forms data is pushed through the Wi-Fi module to the firebase cloud. The result obtained regarding the program proposed is as planned.